2009
DOI: 10.1177/089686080902902s22
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Referral to Pre-Dialysis Services: One Center's Experience

Abstract: The number of patients receiving renal replacement therapy in the United Kingdom is rapidly rising. Chronic kidney disease (CKD) is a worldwide public health problem with significant comorbidity and mortality. Several organizational guidelines have been developed in an attempt to identify when appropriate referral to nephrology services should occur; however, many of these guidelines provide conflicting recommendations on referral. Recent surveys suggest that more than 30% of patients with CKD are referred lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Hence, some studies have shown that quality of life (QOL), assessed by internationally validated questionnaires, is worse in individuals with CKD compared to those without renal disease [ 10 ], and that the morbidity and mortality in end-stage disease are influenced by timing and quality care before the start of dialysis [ 8 , 11 ]. A systematic review of the QOL scores of these patients as a parameter of treatment adequacy is recommended [ 1 ] and it is also suggested that interventions in pre-dialysis are useful and can influence the clinical evolution in the later stages of the disease [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, some studies have shown that quality of life (QOL), assessed by internationally validated questionnaires, is worse in individuals with CKD compared to those without renal disease [ 10 ], and that the morbidity and mortality in end-stage disease are influenced by timing and quality care before the start of dialysis [ 8 , 11 ]. A systematic review of the QOL scores of these patients as a parameter of treatment adequacy is recommended [ 1 ] and it is also suggested that interventions in pre-dialysis are useful and can influence the clinical evolution in the later stages of the disease [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggest delaying PD for 4 - 6 weeks after catheter insertion to accelerate wound healing (8). However, quite a few patients have to start urgently on dialysis because of late referral or unexpected deterioration of residual renal function (9,10). Currently, the optimal duration of the break-in period is still unclear.…”
mentioning
confidence: 99%
“…34, no. 1 PDI Patients were grouped according to the duration of their break-in period (from catheter implantation and to dialysis initiation): 7 days or less (BI ≤7 ), 8 -14 days (BI [8][9][10][11][12][13][14], and more than 14 days (BI >14 ).…”
mentioning
confidence: 99%
“…Early nephrology referral has been associated with multiple advantages, including improved outcomes [45][46][47][48], financial cost of emergent dialysis, psychosocial preparation and modality choice of initial dialysis [49]. In addition, early referral may be associated with slowing of the progression of ESRD, decreasing the need for and duration of hospital admission, higher albumin, relatively lower phosphorus and parathyroid hormone levels, choice of peritoneal dialysis modality and improved quality of life [31,44,45,[50][51][52][53]. Data from a previous prospective cohort study that conducted between 2002 and 2006, suggested that the anemia and progression of left ventricular hypertrophy in the late referral patients during HD treatment are associated with poor survival on HD [54].…”
Section: Discussionmentioning
confidence: 99%